2021
DOI: 10.19184/nlj.v6i1.19228
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Theory of Planned Behavior to Identify Nursing Student's Intention to be a Bystander Cardiopulmonary Resuscitation

Abstract: Background: Theory of Planned Behavior (TPB) is a social pshycological theory which explained that someone's tendency to behave is affected by their intention. This theory often used to predict behavioral intention in health workers by measuring some aspects such as attitude, subjective norm and self efficacy. As a prospective health worker who equipped with knowledge and skills about Cardiopulmonary Resuscitation (CPR) during education phase, nursing students are expected to have a good intentions to become b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…This study found a significant association between attitudes and validation of BLS certificate ( P <0.001). Wati et al 33 found a strong association between attitudes, subjective norms, and self-efficacy and intention.…”
Section: Discussionmentioning
confidence: 99%
“…This study found a significant association between attitudes and validation of BLS certificate ( P <0.001). Wati et al 33 found a strong association between attitudes, subjective norms, and self-efficacy and intention.…”
Section: Discussionmentioning
confidence: 99%
“…Self efficacy in this study has a median of 63.5, where in this category of self efficacy is classified as high (category in score> 52). High self-efficacy in the application of BLS owned by nursing profession students can be because students have been taught about the knowledge and skills on how to carry out BLS during their education so that they tend to get used to dealing with these conditions (Wati, Wihastuti, & Nasution, 2021). The results of the correlation statistical test with Spearman Rank on 70 people showed a significant relationship with a p value = 0.026 (p < 0.05), at a significance level of 0.05 with an r value of 0.266.…”
Section: Univariate Analysis Resultsmentioning
confidence: 99%
“…Nursing students' high self-efficacy for CPR may be related to several things. One of them is that students are prospective health workers who have been taught knowledge and skills on how to do CPR during their education, so they tend to ge t used to dealing with these conditions (Wati et al, 2021). High self-efficacy can also increase self-confidence to act calmly and focused (Nastiti et al, 2021;Desiani et al, 2017).…”
Section: Discussionmentioning
confidence: 99%